Monitoring and Evaluation Practices and Performance of County Maternal Health Programmes - Gatimu, John; Gakuu, Christopher; Ndiritu, Anne (European Scientific Journal, ESJ, 2021)
The study sought to establish the relationship between monitoring and evaluation practices and performance of County Maternal Health programmes in Kenya. The combined monitoring and evaluation practices included planning for M&E, stakeholder engagement, capacity building for M&E, and M&E data use. The study adopted a descriptive survey research design. To obtain 282 respondents, stratified random sampling was used. A self-administered structured questionnaire was the study’s research instrument. Using descriptive narratives, qualitative data was analyzed within specific themes. Quantitative data was analyzed descriptively using measures of central tendencies and measures of dispersion. Regression was conducted for testing the study hypotheses. Data was presented using frequency tables. The study found that stakeholders’ engagement in M&E and capacity building for M&E influenced the performance of County Maternal Health Programmes in Kenya. The study also found that the respondents agreed that planning for M&E and the data management for M&E. This implied that the combined monitoring and evaluation practices influence performance of County Maternal Health Programmes in Kenya.The study found a strong correlation between the performance of county maternal health programmes and combined monitoring and evaluation practices. The study concluded that combined planning for M&E monitoring and evaluation practices influenced the performance of county maternal health programmes. The study suggests that management develop an effective methodology as well as raise awareness of M&E activities for the success of the project. The study also suggests that human resources issues such as workers charged with monitoring and evaluation ought to have technical capabilities, and roles and duties of monitoring and evaluation personnel should be outlined at the start of projects. To ensure M&E sustainability health sector reforms, investments in strong and vibrant technical harmonization platforms that can sustain the change agenda at all times and every required level.